META-ANALYSIS ON THE RISK OF CHRONIC MENTAL HEALTH CONDITIONS IN YOUNG ADULTS - Adehi, M U; Madaki, R M; Chaku, S E; Adenomon, M O; Omole, O O (Economics and Statistics Research Journal (ESRJ), 2025)
The World Health Organization (WHO) conceptualizes mental health as a state of well-being in which individuals realize their own abilities, cope with the normal stresses of life, work productively and fruitfully, and is able to make a contribution to his or her community. With an emphasis on clarifying the patterns, trends, and standardized common effect or variation implications, this study conducts a thorough meta-analysis to assess the risk factors of chronic mental health conditions in young adults using meta-analysis. This study synthesizes data from the body of current literature via published data. This research adopts a systematic approach using a random-effects meta-analysis framework to aggregate findings from peer-reviewed studies conducted between 2002 and 2024. Key outcomes include the pooled risk factors of chronic mental health conditions and the estimated effect sizes of contributing risk factors, such as childhood abuse, social isolation, and food insecurity. The meta-analysis revealed significant risk factors for chronic mental health conditions in young adults, with a mean effect size of 4.94 (95% CI: 4.03 - 5.80, P < 0.001). Substantial heterogeneity was observed among the studies, as indicated by an I² value of 87.7%. This study underscores the critical role that early interventions play in addressing risk factors such as social isolation, childhood abuse, and food insecurity to mitigate the burden of chronic mental health conditions in young adults. The findings emphasize the need for integrated care models that combine clinical, social, and policy-level interventions